A discrete element model of concrete for cyclic loading. (February 2018) - Sinaie, Sina; Ngo, Tuan Duc; Nguyen, Vinh Phu
Highlights: The discrete element method (DEM) is used to develop a cyclic model of concrete. A multi-phase DE model is developed to include the effect of the ITZ. A micro-mechanical damage model is formulated to handle stress reversals. ​Damage is characterized in the micro-mechanical level, and visualized through cracks. An in-house GPU-based computer program is used to reduce the computation runtime. Abstract: This paper takes advantage of the discrete element method to develop a model of concrete for cyclic simulations. For this purpose, a micro-mechanical damage model that also allows stress-reversals is formulated for inter-particle bonds. Moreover, a multi-phase implementation of the discrete element method is developed and used for two distinct reasons. First, to characterize aggregate and mortar particles separately. Second, to allow the effect of the interfacial transition zone to be taken into account. A strict validation approach is taken in this work, whereby the developed model is only calibrated against monotonic stress-strain curves and then evaluated for its performance under cyclic loading. Simulation results are constantly compared against experimental values. These comparisons illustrate the capability of the model to predict cyclic properties of concrete. Progression of damage is discussed in terms of numerical variables and also through the visualization of force chains and crack propagation.